STRATEGI PENINGKATAN PEMASARAN DAN PENJUALAN PRODUK OLAHAN BUAH MANGROVE MELALUI PEMBUATAN WEBSITE - Ubaidillah Umar; Aulia Rahma Annisa; Helmy Widyantara (Politeknik Negeri Sriwijaya, 2023)
Besides being useful for protecting the coast from abrasion, mangrove plants have many other benefits, one of which is the fruit of the mangrove plant. The fruit of this mangrove plant was successfully processed by one of the UKM residents of Medokan Ayu Surabaya, namely